Optimizing Online Learning during Covid 19 Pandemic in Junior High School - Rojif Mualim; M Fachdir Saputra (Universitas Islam negeri Mahmud Yunus Batusangkar, 2021)
Covid 19 pandemic has changed people's life, including education, in Indonesia. This research aims to describe Islamic education (PAI) teachers’ efforts to optimize online learning during pandemics. Descriptive qualitative was chosen as the method of this research. The research subjects were Islamic education teachers at SMPN 7 Sukoharjo, and the informants were teachers, principals, and students at the school. Data were collected by using observation, interview, and documentation techniques. The trustworthiness of data was tested by doing triangulation. Then, the data were analyzed by using an interactive model which consisted of data reduction, display, and verification/concluding. The result of this study indicated that to optimize online learning during the covid 19 pandemics, PAI teachers used various platforms such as Whatsapp, google form, and google meet. The teaching and learning process was done interactively and evaluated by having the mid-term test, final test, and portfolio. Furthermore, the teachers also coordinated with parents about students’ difficulties in online learning, and whenever necessary, the teachers did home visits.